Benign Endobronchial Tumors: A Clinicopathologic Review - Insler, Joshua E.; Seder, Christopher W.; Furlan, Karina; Mir, Fatima; Reddy, Vijaya B.; Gattuso, Paolo (Frontiers in Surgery, 2021)
Purpose: Benign endobronchial tumors are rare entities that can be difficult to diagnose because they often present with non-specific symptoms and vague radiographic findings. The current study reviews the clinical, radiologic and pathologic features, diagnosis, and treatment of patients with benign endobronchial tumors. Methods: We examined the charts of all patients who presented with biopsy-proven benign endobronchial tumors at a tertiary-care academic medical center between 1993 and 2018. Pertinent clinicopathologic and radiologic data were analyzed, with particular attention paid to treatment modalities and mean overall patient survival. Results: A total of 28 cases were identified. The most common benign neoplasm was hamartoma (37%), followed by lipoma (19%), squamous papilloma (11%), pleomorphic adenoma (7%), mucin gland adenoma (7%), papillary adenoma (3%), hemangioma (3%), neurofibroma (3%), leiomyoma (3%), and papillomatosis (3%). Cough (58%), shortness of breath (44%), and hemoptysis (15%) were the most frequent presentations. Most cases demonstrated well-defined submucosal or pedunculated endobronchial lesions with segmental pneumonia or atelectasis on imaging. Histologic diagnosis was obtained by endobronchial resection in 43% of patients, thoracoscopic lobectomy in 36%, endobronchial biopsy in 18%, and thoracoscopic wedge resections in 3%. All procedures were performed with no intraoperative or in-hospital deaths (mean overall survival: 20.2 years). Conclusion: Benign endobronchial tumors typically present as well-defined submucosal and/or pedunculated lesions, and may lead to post-obstructive complications. Endobronchial resection is the preferred strategy for diagnosis and treatment of these tumors.